Ocean acidification has little effect on the biochemical composition of the coccolithophore Emiliania huxleyi. - Heidenreich, Elena; Wördenweber, Robin; Kirschhofer, Frank; Nusser, Michael; Friedrich, Frank; Fahl, Kirsten; Kruse, Olaf; Rost, Bjorn; Franzreb, Matthias; Brenner-WeiSS, Gerald; Rokitta, Sebastian (PLOS ONE, 2019)
Heidenreich E, Wördenweber R, Kirschhofer F, et al. Ocean acidification has little effect on the biochemical composition of the coccolithophore Emiliania huxleyi. PloS one . 2019;14(7): e0218564. Owing to the hierarchical organization of biology, from genomes over transcriptomes and proteomes down to metabolomes, there is continuous debate about the extent to which data and interpretations derived from one level, e.g. the transcriptome, are in agreement with other levels, e.g. the metabolome. Here, we tested the effect of ocean acidification (OA; 400 vs. 1000 muatm CO2) and its modulation by light intensity (50 vs. 300 mumol photons m-2 s-1) on the biomass composition (represented by 75 key metabolites) of diploid and haploid life-cycle stages of the coccolithophore Emiliania huxleyi (RCC1216 and RCC1217) and compared these data with interpretations from previous physiological and gene expression screenings. The metabolite patterns showed minor responses to OA in both life-cycle stages. Whereas previous gene expression analyses suggested that the observed increased biomass buildup derived from lipid and carbohydrate storage, this dataset suggests that OA slightly increases overall biomass of cells, but does not significantly alter their metabolite composition. Generally, light was shown to be a more dominant driver of metabolite composition than OA, increasing the relative abundances of amino acids, mannitol and storage lipids, and shifting pigment contents to accommodate increased irradiance levels. The diploid stage was shown to contain vastly more osmolytes and mannitol than the haploid stage, which in turn had a higher relative content of amino acids, especially aromatic ones. Besides the differences between the investigated cell types and the general effects on biomass buildup, our analyses indicate that OA imposes only negligible effects on E. huxleyis biomass composition.